Bottom-type scattering layers and equatorial spread F - D. L. Hysell; J. Chun; J. L. Chau (Annales Geophysicae, 2004)
Jicamarca radar observations of bottom-type coherent scattering layers in the post-sunset bottomside F-region ionosphere are presented and analyzed. The morphology of the primary waves seen in radar images of the layers supports the hypothesis of kudeki+bhattacharyya-1999 that wind-driven gradient drift instabilities are operating. In one layer event when topside spread F did not occur, irregularities were distributed uniformly in space throughout the layers. In another event when topside spread F did eventually occur, the irregularities within the pre-existing bottom-type layers were horizontally clustered, with clusters separated by about 30km. The same horizontal periodicity was evident in the radar plumes and large-scale irregularities that emerged later in the event. We surmise that horizontal periodicity in bottom-type layer irregularity distribution is indicative of large-scale horizontal waves in the bottomside F-region that may serve as seed waves for large-scale Rayleigh Taylor instabilities. Key words. Ionosphere (equatorial ionosphere; ionospheric irregularties; plasma waves and instabilities)